2009
DOI: 10.1007/s00122-009-1061-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of a new powdery mildew resistance gene Pm41 on chromosome 3BL derived from wild emmer (Triticum turgidum var. dicoccoides)

Abstract: Powdery mildew caused by Blumeria graminis f. sp. tritici is an important wheat disease in China and other parts of the world. Wild emmer (Triticum turgidum var. dicoccoides) is the immediate progenitor of cultivated tetraploid and hexaploid wheats and thus an important resource for wheat improvement. Wild emmer accession IW2 collected from Mount Hermon, Israel, is highly resistant to powdery mildew at the seedling and adult plant stages. Genetic analysis using an F(2) segregating population and F(2:3) familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 48 publications
1
42
0
3
Order By: Relevance
“…Development of resistant germplasm to powdery mildew is based on interspecific hybridization and backcrossing (Murphy;Navarro;Leath, 2002;Navarro et EMARA, H. M. et al al., 2000). To date, 61 powdery mildew resistance genes, mapped to 43 loci (McIntosh;Yamazaki;Dubcovsky, 2008;He et al, 2009;Hua et al, 2009;Li;Fang;Zhang, 2009;Luo et al, 2009) have been identified and formally catalogued in wheat. However, some of the genes, derived from wild relatives, are difficult to use in wheat breeding because of linkage drag (Hospital, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Development of resistant germplasm to powdery mildew is based on interspecific hybridization and backcrossing (Murphy;Navarro;Leath, 2002;Navarro et EMARA, H. M. et al al., 2000). To date, 61 powdery mildew resistance genes, mapped to 43 loci (McIntosh;Yamazaki;Dubcovsky, 2008;He et al, 2009;Hua et al, 2009;Li;Fang;Zhang, 2009;Luo et al, 2009) have been identified and formally catalogued in wheat. However, some of the genes, derived from wild relatives, are difficult to use in wheat breeding because of linkage drag (Hospital, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…dicoccoides, AABB, 2n = 28) is a valuable source of resistance to pathogens, and genes transferred from this species included powdery mildew resistance genes Pm16, Pm26, Pm30, Pm36, Pm41, and pm42, which were transferred to wheat chromosomes 5BS, 2BS, 5BS, 5BL, 3BL and 2BS, respectively (Reader and Miller 1991;Chen et al 2005;Rong et al 2000;Liu et al 2002;Blanco et al 2008;Li et al 2009;Hua et al 2009). There is also potential, largely untapped of the rich genetic resource in wild emmer, for disease resistance, pest tolerance and various abiotic stresses (Xie and Nevo 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among these genes, 16 originate from alien species . Nevertheless, many wheat cultivars seem to have the same few Pm genes, such as Pm2 , Pm4b , Pm5 , Pm6, and Pm8 [Zeller et al, 1993;McIntosh et al, 1998], providing little protection against the contemporary pathogen populations [Limpert et al, 1987;Li et al, 2009]. Some other effective resistance genes, such as Pm1c , Pm12 , Pm13 , Pm16, and Mlxbd , cannot be widely used in breeding programs due to their poor agronomic traits associated with either alien chromosome segments or unadapted genetic backgrounds [Duan et al, 1998;Qiu and Zhang, 2004].…”
Section: Discussionmentioning
confidence: 99%